Relationship of Self Efficacy and Family Support with Compliance Undergoing Therapy for Hypertension Patients in the Work Area of Baumata Publik Health Center - Siti Sakinah; Juandri Seprianto Tusi; Sance Yanidas Metkono (Sean Institute, 2023)
Hypertension is a blood pressure disease in which an individual's blood pressure is above normal values, a condition in which blood vessels are persistently pressurized. The purpose of this research was to analyze the relationship of self efficacy and family support with compliance undergoing therapy for hypertension patients in the work area of Baumata Publik Health Center. This research design uses descriptive analytics with a cross sectional approach. The research was conducted on 173 respondents. The results showed that there was a relationship between self-efficacy and compliance to therapy in patients with hypertension, as evidenced by the results of the Chi-square test, a p-value of 0.003 <0.05. As well as a relationship between family support and compliance to therapy in patients with hypertension, it was proven by the results. Chi-square test obtained p-value 0.000 <0.05. Conclusion: Based on the results of the research, it shows that there is a relationship of self efficacy and family support with compliance undergoing therapy for hypertension patients.